Metabolomic analysis of plasma and brain tissues in fentanyl-induced conditioned place preference mice - Du, Kaili; Ning, Xiaoyu; Han, Yongze; Jiang, Xiaoyu; Wang, Zhuoyi; Wang, Tao; Su, Hongliang; Liu, Ting; Cong, Bin; Cheng, Caixia; Yun, Keming (Frontiers in Pharmacology, 2026)
Fentanyl abuse has been associated with neurological and psychological harm. However, the metabolic changes within the peripheral circulation and central nervous system involved in fentanyl addiction have not been well explored. In the present study, metabolic changes in plasma, caudate putamen (CPu), hippocampus (Hip), and prefrontal cortex (PFC) were investigated in mouse models of drug addiction based on fentanyl-induced conditioned place preference (CPP). Metabolic profiles were measured using untargeted UHPLC-Q-Exactive HFX mass spectrometry. A total of 131, 196, 104, and 52 altered metabolites were identified in plasma, CPu, Hip, and PFC, respectively. The identified metabolites mainly included lipid mediators, carbohydrate metabolites, fatty acids, amino acids (AAs) and their derivatives, and nucleotide metabolites. The disturbed metabolic pathways were primarily involved in lipid metabolism, carbohydrate metabolism, AA metabolism, nucleotide metabolism, and the metabolism of cofactors and vitamins. These findings indicate disturbances in cell membrane metabolism, energy metabolism, AA metabolism, and neurotransmitter systems caused by fentanyl addiction. Our study provides a valuable resource for future investigations aimed at defining the role of metabolites in fentanyl addiction, which may help develop new pharmacotherapies.